Correction to: Why public health matters today and tomorrow: the role of applied public health research - McLaren, Lindsay; Braitstein, Paula; Buckeridge, David; Contandriopoulos, Damien; Creatore, Maria I.; Faulkner, Guy; Hammond, David; Hoffman, Steven J.; Kestens, Yan; Leatherdale, Scott; McGavock, Jonathan; Norman, Wendy V.; et al. (Canadian journal of public health, 2020)
The article "Why public health matters today and tomorrow: the role of applied public health research," written by Lindsay McLaren et al., was originally published Online First without Open Access.The article "Why public health matters today and tomorrow: the role of applied public health research," written by Lindsay McLaren et al., was originally published Online First without Open Access.